The Effect Of Glucose Concentration On The Co-Factor Recycling In A Non-Growing Whole-Cell Saccharomyces Cerevisiae-Mediated Ketoisophorone Biotransformation - Umapathy, Nanthini (Universiti Sains Malaysia, 2017)
The aim of this study is to investigate the effect of different glucose concentrations on the recycling of co-factor in a non-growing whole-cell Saccharomyces cerevisiae. Besides that, this study also investigates the effect of different glucose concentrations on the biotransformation of 2,6,6-trimethylcyclohex-2-ene-1,4-dione also known as ketoisophorone in a non-growing whole-cell S. cerevisiae. The liquid phase biotransformation was carried out in a shake-flask culture. The conditions of biotransformation are 37 °C, 150 rpm, 5 g/L S. cerevisiae, 0.2 g/L ketoisophorone and varied concentration of glucose (5 g/L, 10g/L, 15 g/L). It was found that level of co-factors were shown at different glucose concentrations. This indicates that co-factor recycling process exist in this reaction.15 g/L of glucose showed the highest value of absorbance which is 0.4100. 5.018×1022 number of glucose molecules are present in 15 g/L glucose. The optimum concentration of glucose for the formation of actinol is 15 g/L. 15 g/L of glucose showed a maximum of 12 mole % of actinol formed. Levodione was the only intermediate formed during the biotransformation. Ketone reduction did not occur due to the inhibition of alcohol dehydrogenase caused by high concentration of NAD+. Besides, ketone reduction has a slower reaction rate as compared to the reduction of carbon-carbon double bond by enoate reductase.